Epidemiological analysis of Dirofilaria immitis (Spirurida: Onchocercidae) infecting pet dogs (Canis lupus familiaris, Linnaeus, 1758) in Baixada Fluminense, Rio de Janeiro - de Andrade Vieira, Viviane Marques; da Silva, Priscila Pinho; Paulino, Érica Tex; do Amaral Fernandes, Priscila; Labarthe, Norma; Gazêta, Gilberto Salles; de Moraes Neto, Antonio Henrique Almeida (Frontiers in Veterinary Science, 2024)
Dirofilaria immitis infection is routinely detected in dogs during veterinary care in tropical and subtropical regions worldwide. Parasitological tests for the detection of this infection are routinely performed only in areas with a high prevalence. Baixada Fluminense, a region in Rio de Janeiro, was considered heartworm-free until local veterinarians began to receive blood exams results indicating the presence of microfilariae (MF). A laboratory database was hence used to collect data from 2017 to 2020 to understand the extent of spread of the parasite in this area. The results of complete blood count analysis and MF or heartworm antigen detection tests conducted on canine samples sent from veterinary clinics in Baixada Fluminense (Magé, Duque de Caxias, Guapimirim, Nova Iguaçu, and São João de Meriti municipalities) were included. In total, the results of 16,314 hematological tests were considered. The overall prevalence of D. immitis was 3.4% (554/16,314), considering that only one test result was obtained per animal on the same day. This study is highly relevant because it indicates the spreading geographic distribution of the worms, heightens awareness among local health professionals and the general population, and encourages compliance with prophylactic measures to prevent further spread of parasite.